Adherence to the Use of Compressive Therapy in Varicose Veins: A Review Article - Karmacharya, Robin Man; Kunwar, Kajol; Dahal, Sushil; Bhat, Swechha (Annapurna Journal of Health Sciences, 2023)
Varicose veins (VV) are engorged veins mainly found in the peripheral regions. The presence of varicosities is not only a cosmetic problem but results in discomfort, loss of working days, disability, and health-related quality of life. Compression therapy is the most widely used conservative treatment for VV. Its effectiveness depends upon patient adherence. Here, we discuss the various modes of compression therapy and the factors affecting its adherence among varicose veins patients.